Web design : E-commerce. - Wiedemann, Julius, ....- (Köln : Taschen)
In this latest addition to the Web Design series, we explore the very best of electronic commerce website design. Now that people are using online shops to buy everything from computers to groceries to clothing, e-commerce has become a major player in the sales market - to such a degree that recent research has estimated that about 10% of US brick and mortar sales are even influenced by online shops. From small retailers to online superstores, this guide brings you the most cutting edge e-commerce sites on the web today.